Synthesis of chalcones bearing 2-hydroperoxy-3-methyl-3-butenyl or 2-hydroxy-3-methyl-3-butenyl group from prenylated chalcones. Issue 10 (18th May 2020) - Sugamoto, Kazuhiro; Yoshifuji, Toru; Soejima, Shuhei; Honda, Yoshihiro
Abstract: Chalcones bearing 2-hydroperoxy-3-methyl-3-butenyl or 2-hydroxy-3-methyl-3-butenyl groups, such as xanthoangelol E (1a), xanthoangelol D (2a ), psorachalcone A (2 b ), xanthohumol D (2c ), and related derivatives were first synthesized by using the ene reaction of prenylated chalcones with singlet oxygen. Graphical Abstract: